The Relationship Between Self-Esteem and Narcissism With Self-Presentation on Social Media Among Generation Z - Citra Puspita Ayu Pranata; Rr Amanda Pasca Rini; Nindia Pratitis (unprimdn.ac.id, 2025)
Intense social media use among Generation Z has led to idealized self-presentation behavior that often does not align with reality. This study aims to examine the relationship between self-esteem and narcissism with self-presentation on social media in Generation Z, both partially and simultaneously. The subjects of the study were 151 respondents from Generation Z who were active on social media platforms. Using a quantitative approach, the data were analyzed through a regression test. The results showed that narcissism had a significant correlation with self-presentation (t = 2.397, p = 0.018), while self-esteem did not show a significant relationship (p = 0.270). Simultaneous analysis showed that self-esteem and narcissism together influenced self-presentation with a sig value of 0.010. Although the contribution of narcissism is more dominant, with a practical contribution of 4.6%, overall, these two variables only explain a small part of the factors that influence self-presentation (R² = 0.060). Thus, narcissism is a dominant factor in self-presentation behavior, while the contribution of both to the model is still limited. This study recommends exploring additional psychological variables to gain a more comprehensive understanding.